Inequality, the financial crisis and stagnation: Competing stories and why they matter - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2015)
This paper examines several mainstream explanations of the financial crisis and stagnation and the role they attribute to income inequality. Those explanations are contrasted with a structural Keynesian explanation. The role of income inequality differs substantially, giving rise to different policy recommendations. That highlights the critical importance of economic theory. Theory shapes the way we understand the world, thereby shaping how we respond to it. The theoretical narrative we adopt therefore implicitly shapes policy. That observation applies forcefully to the issue of income inequality, the financial crisis and stagnation, making it critical we get the story right. – – Diese Arbeit untersucht mehrere Erklärungsansätze für die Finanzkrise und die darauf folgende wirtschaftliche Stagnation sowie die Rolle, die sie der Einkommensungleichheit zuschreiben. Diesen Erklärungen wird eine strukturelle keynesianische Erklärung entgegengesetzt. Die Rolle von Einkommensungleichheit variiert substanziell und führt somit zu verschiedenen Empfehlungen an die Politik. Hier wird die Wichtigkeit ökonomischer Theorie sichtbar. Theorie bestimmt, wie wir die Welt verstehen und somit wie wir auf sie reagieren. Das theoretische Narrativ, das wir entwickeln bestimmt somit auch implizit die empfohlene Politik. Dies trifft um so mehr zu, wenn es um Ungleichheit geht, die Finanzkrise und ökonomische Stagnation, umso wichtiger ist es, einen richtigen Blick auf die Dinge zu bekommen.
Keywords: E00; E02; E10; E20; E24; 330; income inequality; financial crisis; stagnation; economic theory